(untitled) (Bangladesh Journal of Nutrition, 2014)
Quail is quiet familiar bird in Bangladesh but its egg is not as popular as that of hen or duck though, their low cost of production and low risk of diseases. To compare the nutritional value among the quail, hen and duck egg, a study was carried out by collecting the sample from different poultry farm around Dhaka city. After analyzing the three types of egg it was found that moisture content was highest in hen’s egg (77.33+0.19g /lOOg), as compared to Quail’s egg (72.83+0.85g/I00g) and Duck’s egg (70.59+0.39g/100g). Protein content was almost same in quail’s egg (15.29+0.43/100g) and duck’s egg (15.13+0.27g/100g) but lower in hen’s egg (12.76+0.23g/100g). Slight difference in fat content was found among three types of egg, the values being 13.22+0.16g/100g, 13.47+0.16g/100g and 13.15+0.69g/100g respectively for Hen, Duck and Quail’s egg. Total mineral content was almost same in duck’s egg (1.23+0.04g/100g) and quail eggs (1.26+0.05g/100g), but the value was slightly low in hen eggs (1.03+0.09g/100g). The value of cholesterol in quail’s egg (422.88+11.5mg/100g) was lightly greater than that of hen’s egg (373.76+lO.lmgAOOg), but in case of duck’s egg it was537.05+3.3mg/100g. It indicates that cholesterol content in duck egg was far higher than that of quail’s egg and hen’s egg. At the end of the study it is inferred that nutritive value of the quail egg was better than hen eggs in aspect of protein and mineral content. Bangladesh J. Nutr. Vol. 26-27, December 2014, P: 35-39